Gender and racial discrimination in pay and promotion for NHS nurses - Stephen Pudney; Michael A. Shields (Institute for the Study of Labor (IZA), 1999)
For many years the NHS has been subject to allegations that gender and racial discrimination are a feature of the internal labour market for qualified nurses. This paper examines this issue with regard to the promotion process using 1994 survey data. We start by rejecting the assumption of covariate exogeneity inherent in the ordered probit model. A full simultaneous model is then developed which has important consequences for estimates of the influence of gender, ethnicity, training and career interruptions. We find evidence of significant differences in speed of promotion between gender and ethnic groups, which imply large differences in career earnings.
Keywords: C5; J3; I1; J7; 330; Nursing; promotions; gender; ethnicity; ordered probit models; endogeneity; Pflegeberufe; Ethnische Gruppe; Geschlecht; Erwerbsverlauf; Lohndifferenzierung; Schätzung; Großbritannien